Multidimensional security concept and its implications for post-cold war Europe and Turkey - Cebeci, Münevver (My University, 2004)
This study aims at sorting out the differences between the Turkish and European conceptions of security in the post-Cold War era and the impact of these differences on Turkey's quest for membership in the European Union (EU). To realise this aim, the study is composed of one major argument and a set of supporting arguments. The major argument of this study is that security is crucial for any analysis on the issue of Turkey's accession to the EU; not in terms of what Turkey can offer with regard to military security to the Union but rather in terms of the logic of security which inherently involves the breaking of the normal political rules of the game (as suggested by the Copenhagen School) - i.e. limits on fundamental rights and freedoms as well as on pluralism and democracy. The first chapter sets the theoretical framework of this study; analysing the existing literature on the multidimensional concept of security (which attaches equal significance to non-military and military dimensions of security). The Copenhagen School's approach is emphasised in this chapter as it forms the point of departure of the study. In the second chapter, theories which are closely related to the multidimensional security concept; the two worlds view (zones of peace and conflict), democratic peace theory and the theory of security communities are scrutinized with a view to supporting the theoretical basis established in the first chapter. In the third and fourth chapters, the nature of the EU as a de-securitization process and a civilian power, and, Turkey's nature as an over-securitizing actor are all put forward respectively, in an effort to develop the major argument of this study. The fifth chapter consists of a comparative analysis of the security conceptions and perceptions of Turkey and the EU, in order to display the interplay of security identities between the two entities. This chapter lays down the areas of convergence and divergence between Turkey and the EU in this respect. The study reaches the conclusion that despite differences in their perception and conception of security; Turkey and the EU have also found grounds for convergence in this regard. Turkey has started a period of de-securitization in line with its quest for EU membership, whereas the EU has started re-securitization, especially after September 11.

Bu doktora çalışmasının amacı, Soğuk Savaş dönemi sonrasında Türkiye ve Avrupa'daki güvenlik kavramı farklılıklarını ortaya koymak ve söz konusu farklılıkların Türkiye'nin Avrupa Birliği (AB) üyesi olma hedefine etkilerini incelemektir. Çalışma, bir ana argüman ve destekleyici yan argümanlardan oluşmaktadır. Ana argüman; güvenlik kavramının, Türkiye'nin AB'ye girişi ile ilgili herhangi bir analiz için çok önemli olduğudur. Ancak bu önem, Türkiye'nin askeri güvenlik konusunda Birliğe olası katkısıdan çok, güvenliğin teorik tanımının içerdiği öğeler ile ilgilidir. Çünkü, güvenlik, özünde (Kopenhag ekolü tarafından önerildiği üzere) oyunun normal siyasi kurallarını bozan - bir başka deyişle, çoğulculuk, demokrasi ve temel hak ve özgürlükleri kısıtlayıcı - öğeleri barındırır. boyutlu güvenlik kavramı (bu kavram güvenliğin askeri ve askeri olmayan boyutlarına eşit önem verir) üzerinde yapılmış akademik çalışmaları inceleyerek, tezin teorik çerçevesini çizmektedir. Kopenhag ekolünün yaklaşımı, tezin hareket noktasını oluşturduğu için, bu bölümde yoğunlukla vurgulanmaktadır. İkinci bölümde, çok boyutlu güvenlik kavramı ile yakından ilgili teoriler; iki dünya görüşü (barış ve çatışma alanları), demokratik barış teorisi ve güvenlik toplumları teorisi, ilk bölümdeki teorik temeli pekiştirmek amacı ile incelenmektedir. Üçüncü ve dördüncü bölümlerde, sırasıyla, AB'nin bir de-securitization (meseleleri güvenlik alanından çıkarıp, normalleştirme) süreci ve sivil güç olarak yapısı ve Türkiye'nin fazla güvenlikleştirme (over-securitization) yapan bir aktör olarak doğası, bu tezin ana argümanını geliştirmek üzere ele alınmaktadır. Beşinci bölüm, Türkiye ve Avrupa'nın güvenlik kimliklerinin karşılıklı etkileşimlerini ortaya koymak amacı ile bu iki entitenin güvenlik anlayış ve algılayışlarını karşılaştıran bir analizden oluşmaktadır. Bu bölüm, söz konusu alanlarda Türkiye ve AB arasındaki ayrışma ve birleşme noktalarını tespit etmektedir. Çalışma, aralarındaki güvenlik anlayışı ve algılayışı farklılıklarına rağmen, Türkiye ve AB'nin bu konuda birleşme noktalarının da bulunduğu sonucuna varmaktadır. Türkiye, AB üyeliği hedefine uygun olarak bir de-securitization dönemine girmiş; AB ise, özellikle 11 Eylül sonrasında bir yeniden güvenlikleştirme (re-securitization) sürecine başlamıştır ve bu gelişmeler iki taraf arasındaki en onemli birleşme noktasını oluşturmaktadır.
Keywords: Avrupa Birliği